2012
DOI: 10.1108/17506181211265077
|View full text |Cite
|
Sign up to set email alerts
|

Non‐response bias in internet‐based advertising conversion studies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…However, a statistically significant ( t = 5.818, df = 134,984, p = .000) difference of $42.85 was found between the unweighted sample ($598.74) and the weighted sample ($641.59) for mean total destination expenditure. This finding indicates that use of the unweighted sample results in an underestimation of approximately 6.7 percent and is consistent with the findings of Park and Fesenmaier (2012). Therefore, the results discussed in this paper are based on a weighted sample that corrects for response bias.…”
Section: Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…However, a statistically significant ( t = 5.818, df = 134,984, p = .000) difference of $42.85 was found between the unweighted sample ($598.74) and the weighted sample ($641.59) for mean total destination expenditure. This finding indicates that use of the unweighted sample results in an underestimation of approximately 6.7 percent and is consistent with the findings of Park and Fesenmaier (2012). Therefore, the results discussed in this paper are based on a weighted sample that corrects for response bias.…”
Section: Methodssupporting
confidence: 87%
“…Respondent email addresses were obtained separately for each of the 40 destination advertising campaigns and, in total, 264,317 online surveys were successfully delivered to American travelers 18 years and older. This aspect of the methodology is important in that it avoids selection bias based on destination which leads to a more precise analysis of tourist demand as it includes not only those people who travel and purchase but also those who do not (Park and Fesenmaier 2012). In order to increase the response rate, the following three-step process was followed: (1) an initial invitation was sent out along with the URL of the survey; (2) four days later, a reminder was delivered to those who had not completed the survey; and (3) the final request for participation was sent out to those who had not completed the survey one week later.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, this study used the inverse propensity scores as a weighting adjustment technique to quantify any possible nonresponse error (Rosenbaum and Rubin 1984). The collected data were then reweighted based on several known characteristics of the study population (i.e., PRIZM segment, market area, the state of residence, and advertising campaign), as described in Park and Fesenmaier (2012). The unweighted and weighted samples were compared to determine whether or not nonresponse statistically significant bias was present in a given survey.…”
Section: Methodsmentioning
confidence: 99%
“…Decision makers may make costly mistakes because of misleading insights about account performance. For instance, Park and Fesenmaier (2012) found that using unweighted data to estimate advertising effectiveness may lead to considerable over estimation of success. Because SEA campaigns use a multitude of independent variables, there is a need for robust metrics that account for the combined influence of factors operating within SEA campaigns.…”
Section: Introductionmentioning
confidence: 99%